Quantitative analysis for management - Render, Barry; Stair, Ralph M.; Hanna, Michael E. (Upper Saddle River, N.J. Pearson Education, 2009)
For courses in Management Science or Decision Modeling. Render/Stair/Hanna puts an emphasis on model building and computer applications to show students how the techniques presented in the book are used in business.
Chapter 1. Introduction to quantitative analysis -- Chapter 2. Probability concepts and applications -- Chapter 3. Decision analysis -- Chapter 4. Regression models -- Chapter 5. Forecasting -- Chapter 6. Inventory control models -- Chapter 7. Linear programming models : graphical and computer methods -- Chapter 8. Linear programming modeling applications : with computer analyses in Excel and QM for Windows -- Chapter 9. Linear programming : the simplex method -- Chapter 10. Transportation and assignment models -- Chapter 11. Integer programming, goal programming, and nonlinear programming -- Chapter 12. Network models -- Chapter 13. Project management -- Chapter 14. Waiting lines and queuing theory models -- Chapter 15. Simulation modeling -- Chapter 16. Markov Analysis -- Chapter 17. Statistical quality control.
Keywords: Management science; Operations research